The Influence of Online Customer Reviews and Product Quality Perception on Skintific Purchase Decisions on Tiktok Shop - Ayu Nabila Fransiska; Liling Listyawati; Andry Herawati; Damajanti Sri Lestari (Harmony Management: International Journal of Management Science and Business, 2025)
This study is intended to identify the impact of Online Customer Reviews and Product Quality Perceptions on Skintific Purchase Decisions on TikTok Shop. This study applies a quantitative approach through causal methods. Involving 96 respondents who have purchased and used Skintific products on the platform. Data analysis was carried out through the stages of classical assumption tests (normality, multicollinearity, and heteroscedasticity), and used multiple linear regression to test the research hypothesis. The findings show that online customer reviews and product quality perceptions have a positive and significant influence on purchase decisions, both when tested individually and together. The adjusted coefficient of determination (Adjusted R²) reaches 0.875, which means that 87.5% of the variation in purchase decisions can be explained by the two independent variables, while the remaining 12.5% is influenced by external elements outside of this model. Among the two variables studied, Online Customer Reviews were proven to have a dominant influence on Purchase Decisions, with a higher Beta value than Product Quality Perception. This conclusion emphasizes that positive reviews from customers and a good view of product quality are the main drivers for consumers to purchase Skintific products on TikTok Shop. Thus, companies are advised to maintain product reputation through consistent quality as well as optimize digital communication strategies based on customer reviews to improve consumer purchasing decisions.